Perception and Adoption of Famers to Soil and Water Conservation Practices in Upper Turkwel Watershed in Kenya - Toromo, A. K.; Ucakuwun, E. K.; Kipkorir, E. C. (Africa Environmental Review Journal, 2022)
This study was carried out in Kapenguria area of Upper Turkwel Dam in West Pokot County with an objective of determining the factors that influence the perception and adoption of soil and water conservation practices by farmers in the area. A structured questionnaire was used to collect information on household head characteristic, land tenure, crop yield trends and adoption of conservation measures among others. The study used purposeful sampling such that areas selected included both highland and lowland farmers so as to reflect the entire watershed. Data was collected from 100 farmers using face-to-face interviews spread over 12 sub locations with 50% each from highland and lowland. The data was analyzed using SPSS Version 23 and description derived from tables accordingly. Based on the study 98% of the farmers recognized that soil and water conservation had the overall effect of increasing crop production and therefore good for sustainable development. The result showed that the majority (69%) of the farmers interviewed had used SWC structures on their farms but a few had stopped citing lack of funding and lack of technical knowhow among others. Majority of the farmers (77%) in the survey area acknowledged decreased crop production in especially the lowlands where steady decline in maize yield was observed from 2013 to 2016. The yield declined from 6.83(90kg bag of maize yield) in 2013 to 4.86 bags of maize per acre in 2016. Future conservation efforts should put in place measures to address the issues of lack of sustainability after project implementation. The study concludes that clear understanding of the benefits of SWC measures by farmers is a remedy that can assure conservation and sustainability once conservation projects were stopped. Based on the study, approaches that enhance farmer training, understanding and active involvement in soil and water conservation from project inception was necessary and not mere technical support from the development agencies if conservation sustainability was to be realized.